2018
DOI: 10.1039/c7cp04878e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different organic solvents on sodium ion storage in carbon nanopores

Abstract: In this study fully atomistic grand canonical Monte Carlo (GCMC) simulations have been employed to study the behaviour of an electrolyte salt (NaPF) and different non-aqueous (organic) solvents in carbon nanopores, to reveal the structure and storage mechanism. Organic solutions of Na and PF ions at 1 M concentration were considered, based on the conditions in operational sodium ion batteries and supercapacitors. Three organic solvents with different properties were selected: ethylene carbonate (EC), propylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…DFT and MD simulations have shown that the pore structure of carbonaceous anodes directly influences the anode performance. [142,[211][212][213][214][215] From experimental characterization, both planar and curved pore motifs are present in nanoporous hard carbon. The exact contribution to anode performance of different pore shapes and size can be probed from computational studies, allowing for pore engineering to be conducted at an experimental stage.…”
Section: Effect Of Pore Shape and Size On Adsorption And Storagementioning
confidence: 99%
“…DFT and MD simulations have shown that the pore structure of carbonaceous anodes directly influences the anode performance. [142,[211][212][213][214][215] From experimental characterization, both planar and curved pore motifs are present in nanoporous hard carbon. The exact contribution to anode performance of different pore shapes and size can be probed from computational studies, allowing for pore engineering to be conducted at an experimental stage.…”
Section: Effect Of Pore Shape and Size On Adsorption And Storagementioning
confidence: 99%
“…The tunable micro/nanostructure properties of carbonaceous materials could involve the meso/nanopores, the amounts of defects, and certain functional groups. They are likely to affect the existing states of solvents or sodium salts near or on the surfaces of carbonaceous materials to some extent, including difficulty in the desolvation of sodium ions, the distribution gradient of solvent molecules, and the coupling strength of anions and cations, , making the situation near or on the anode surface quite different from those in the parent electrolyte. It should be noted that the micropores could even possibly influence the internal distribution of the interphase composition .…”
Section: Interphase Associations With Electrodesmentioning
confidence: 99%
“…These pores have a wide range of pore diameters (which could also be referred to as interlayer distances for the planar graphitic layer micropores), ranging up to around 5 nm. [ 29,30,36,37 ] Experimental studies have shown that the interlayer distance of the planar graphitic layers in hard carbons has a direct influence on the ability to insert and extract Na, with interlayer distances of up to 8 Å reported. [ 29,30 ] It has also been shown that, apart from the planar graphitic layers, curved and rumpled domains are present in hard carbon systems.…”
Section: Introductionmentioning
confidence: 99%